Antifungal efficacy of lasers against dermatophytes and yeasts in vitro. (September 2013) - Paasch, Uwe; Mock, Andrea; Grunewald, Sonja; Bodendorf, Marc O.; Kendler, Michael; Seitz, Anna-Theresa; Simon, Jan C.; Nenoff, Pietro
Abstract Purpose: Approximately 2–13% of the world population suffers from onychomycosis. Recently, lasers have been introduced for treatment. However, no effect was found with in vitro laser irradiation of pathogens on agar plates. This study aimed to investigate the efficacy of laser irradiation against fungi using an alternative in vitro approach. Materials and methods: Lasers of 808, 980 and 1064 nm were used to heat cell culture media and a nail clipping. Trichophyton rubrum. T. interdigitale. Microsporum gypseum. Candida albicans. C. parapsilosis, and C. guilliermondii species were subcultured and subjected to laser treatments (808/980 nm: 9–27 J/cm2, 6 ms, 12 × 12 or 12 × 50 mm and 1064 nm: 50–240 J/cm2, 90 ms, 5–10 mm). After irradiation, the fungal elements were transferred onto agar plates using conventional and Drigalski spatulas and were incubated for 6 days. Results: The highest increase in temperature was found using a 980-nm laser with a pulse duration of 6 ms and a fluence of 27 J/cm2. The histology work-up revealed a dissection of the nail plate from the nail bed tissue after laser irradiation. Growth inhibition was only found for C. guilliermondii and T. interdigitale. All other pathogens presented only reduced growth, and C. albicans growth was unaffected. Conclusions: This study demonstrates a clear thermal effect for linear scanning 980-nm and long-pulsed 1064-nm laser systems on either nail clippings or cell culture media. Complete pathogen growth impairment was achieved if temperatures were measured above 50 °C. The results for the 1064-nm system were almost comparable to 980 nm results.